Wrist pain in gymnasts: A review of common overuse wrist pathology in the gymnastics athlete - Benjamin, H. J.; Engel, S. C.; Chudzik, D. (Current Sports Medicine Reports, 2017)
Injury rates among gymnasts are among the highest of any sport at the high school and collegiate level per athletic exposure. The wrist has increased injury risk due to repetitive physical stresses predisposing it to acute injury, overuse, and degenerative damage. This article will review the most common overuse wrist injuries seen in gymnasts. Prompt evaluation and management is necessary to avoid the negative sequelae that can often accompany these injuries. Little is known about effective sport-specific injury prevention strategies, but general guidelines for overuse injury prevention including limiting excessive loading of the wrist, maintaining wrist joint flexibility, an emphasis on proper technique, and incorporating wrist and general core strengthening seem beneficial. General return to play principles are similar for all gymnast-related wrist injuries, including resolution of pain, restoration of normal wrist joint function, completion of a progressive rehabilitation program, and use of proper technique.